Method to Solve Linear Differential Equations and Three Independent Variables - Russell Hassan Naser (Journal of Global Pharma Technology, 2018)
In this paper, we find the solution of kinds of linear partial differential, equations of variable coefficients and which have the general form as Hence,…are variable coefficients. By using some assumptions, we will transform the previous equation into the non-linear second order, ordinary differential equationsKeywords: Linear Partial, Differential Equations; Third Order; Three Independent, Variables Academic Discipline and Sub-Disciplines Applied Mathematics, Differential Equations.